Pengembangan E-LKPD Berbasis Kearifan Lokal Mata Pelajaran IPAS Bab 5 Kelas IV SDN 02 Sungai Rumbai - M. Anggrayni; Khairita, Martiya Nurni; Riski, Fidiatul Ayu (Information Technology Education Department, 2024)
This research is based on problems in learning, namely the lack of enthusiasm of students in completing student worksheets (LKPD) and the absence of the introduction of local wisdom in the learning process. The purpose of this study was to develop E-LKPD based on local wisdom for IPAS Chapter 5 Class IV subjects, to add to the existing teaching materials at school and produce E-LKPD that is valid, practical, and effective so that it can improve student learning outcomes at SDN 02 Sungai Rumbai. This research is development research using the R&D (Research and Development) method with the ADDIE model. The sample of this development research is all fourth-grade students of SDN 02 Sungai Rumbai. Based on the research that has been carried out, namely development research, the implications obtained from this development research are E-LKPD IPAS based on Class IV Local Wisdom can help and facilitate educators in the learning process. By using E-LKPD, learning has been organized systematically and interestingly, so that the learning process is carried out effectively and efficiently. E-LKPD can arouse the enthusiasm for learning and activeness of students in learning. E-LKPD can help and facilitate educators in teaching in the classroom because E-LKPD is developed in accordance with learning steps and there are instructions for use.